1999
DOI: 10.1097/00000658-199902000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soybean Oil Emulsion and Eicosapentaenoic Acid on Stress Response and Immune Function After a Severely Stressful Operation

Abstract: Soybean oil emulsion amplifies, and the supplementation of EPA reduces, the stress response and stress-induced immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 23 publications
0
51
3
Order By: Relevance
“…Both pathways require cell-to-cell contact and rely on surface receptors for activation (35). Several studies report death receptor-mediated tumor cell apoptosis by NK cells (36), and physiologic stress was shown to suppress FasL-mediated NK activity (37,38). Indeed, the current study showed that the expression of FasL on NK cells decreased following surgery and that our drug treatment counteracted this effect.…”
Section: Sectionmentioning
confidence: 47%
“…Both pathways require cell-to-cell contact and rely on surface receptors for activation (35). Several studies report death receptor-mediated tumor cell apoptosis by NK cells (36), and physiologic stress was shown to suppress FasL-mediated NK activity (37,38). Indeed, the current study showed that the expression of FasL on NK cells decreased following surgery and that our drug treatment counteracted this effect.…”
Section: Sectionmentioning
confidence: 47%
“…Following evaluation of the title/abstract, 122 papers were deemed potentially relevant and obtained in full. Upon reading the full text of these 122 papers, 62 complied with the inclusion criteria and were included in the review (21,46,47,51,52,54,. The study details are provided in Appendix A (available upon request).…”
Section: Resultsmentioning
confidence: 99%
“…The majority (n=23) utilised ETF, with only 4 studies using ONS (84,104) or a combination of oral and tube routes (46,82). The type of cancer varied; most (n=24) were gastrointestinal (46,76,80,(82)(83)(84)(85)(86)90,93,98,(102)(103)(104)111,112,115,117,118,120,(123)(124)(125)127), with 3 studies on patients with head/neck (116,126) and liver cancer (122).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations